Religious Possession and Self-Repossession: The Black Nationalist Movements and the Anglophone Caribbean Ritual Plays in the 1960s–1970s - Li, Xin (Religions, 2024)
Since achieving political independence in the 1960s, Anglophone Caribbean nations have faced the urgent task of exploring cultural independence. In the socio-cultural sphere, Black nationalism dominated, with Pan-Africanism and Rastafarianism exerting significant influence. In literary creation, writers and intellectuals sought to unearth local popular religions and folk traditions to produce literature that was distinctively Caribbean. In this quest, rituals—especially those involving religious possession—emerged as pivotal tools for writers to explore historical traditions and reflect on identity formation. Ritual plays, in particular, vividly represented these dynamics within the socio-cultural context. This paper examines the interaction between Black nationalist movements and ritual plays during this period, highlighting their significant role in shaping Caribbean identities. It reveals that ritual plays such as Dream on Monkey Mountain, Couvade, and An Echo in the Bone challenge Pan-Africanism promoted by Black nationalist movements. Instead, they employ ancestor possession rituals and elements from multiple religious rituals to construct a native Caribbean identity. These plays underscore the central role of Afro-Caribbean traditions while also highlighting the region’s diverse cultural heritage and the localized nature of Caribbean identity. Furthermore, they broaden the use of religious rituals in recalling and understanding traditions.